Densidade de estocagem na larvicultura e no manejo alimentar de juvenis de pacamã Lophiosilurus alexandri - Nelmara Inês Santos Cordeiro (2012)
The aim of this study was to evaluate different stocking densities in larviculture and feed training of Lophiosilurus alexandri and subsequently, the effect of feeding management on performace of juveniles in two size classes. In the first experiment, juveniles with 30.6 ± 1.4 mm were subjected to feed training using different amounts of Artemia nauplii in mixture of semi moist diets. The second experiment was divided into two phases. In the first phase, larvae with eight days post hatching were stoked at densities of 60, 120, 180, 240 and 300 larvae L-1 and fed Artemia nauplii during the first 15 days of active feeding. In the second phase, lasting 20 days, juveniles of each density were pooled and redistributed at densities of 5, 10, 15, 30 and 40 juveniles L-1 and subjected to feed training based on the result of experiment 1. In the third experiment, trained juveniles were divided into two size classes and fed two different diets for another 20 days. In the experiment 1, the different amounts of Artemia nauplii in the diets provided similar results (P>0.05) of survival and performace. In the first phase of the experiment 2, the different stocking densities did not affect (P>0.05) performace and survival. In the second phase, the performace was similar (P>0.05). However, the survival was lower (P<0.05) for the highest densities tested. The cannibalism was greater (P<0.05) at densities 30 and 40 juveniles L-1. For the third experiment were found effects of inicial size and a diet on performace of juveniles. The larviculture and feed training of L. alexandri can be performed successfully in different stocking densities, being important to consider the particle size of the diet in the subsequent rearing phase.